Preparation of Lignocellulose-Based Activated Carbon Paper as a Manganese Dioxide Carrier for Adsorption and in-situ Catalytic Degradation of Formaldehyde - Zhang, Xiao; Zhang, Chunhui; Lin, Qixuan; Cheng, Banggui; Liu, Xinxin; Peng, Feng; Ren, Junli (Frontiers in Chemistry, 2019)
Formaldehyde is a colorless, highly toxic and flammable gas, which is harmful for human health. Recently, many efforts have been devoted to developing the activate carbon to absorb formaldehyde. In this work, lignocellulose-based activated carbon fiber paper (LACFP) loaded by manganese dioxide (MnO2) was fabricated for the adsorption and in-situ catalytic degradation of formaldehyde. LACFP was prepared by two-stage carbonization and activation of sisal hemp pulp-formed paper, followed by the impregnation of in the manganese sulfate (MnSO4) and potassium permanganate (KMnO4) solutions, and then MnO2 was formed by in situ growth based LACFP by calcination. The catalytic performance of MnO2-loaded LACFP was also discussed for formaldehyde. It was found that the suitable carbonization conditions were elevated, ranging from room temperature to 280 oC at 10 oC/min, from 280 oC to 400 oC at 2 oC/min, being kept temperature at 400 oC for 1 h, and then giving a noticeable rise in temperature from 400 to 700 oC at 15 oC/min. And the activation condition was similar with the carbonization in addition to holding at 700 oC for 2 h. Those conditions mentioned above were optimized to maintain the fiber structure and paper shape integrity, being conducive to loading of catalytic active substances. For the catalytic activity of MnO2-loaded LACFP, the concentration of formaldehyde decreased by 59±6 ppm and the concentration of CO2 increased by 75±3 ppm, when the reaction proceeded at room temperature for 10 h. The results indicated that MnO2-loaded LACFP could catalyze formaldehyde into non-toxic substance.